SPOUTED BED COMBUSTION AND COMBUSTION EFFICIENCY OF THAI LIGNITE CHAR - Woogvicba, Dr.Prasong (Engineering and Applied Science Research, 2013)
The combustion of Thai lignite char has been experimentally studied in a 92 mm spouted bed combustor under a variety of major as combustion efficiency and losses are assessed as high as 89 to 98.5% of combustion efficiency operating conditions. Performance expressed and discussed. Results obtained shows that can be achieved under particle feed size ranging from 2.00-4.00 mm, with excess air varying from 107-185 %. The most influential variable affecting combustion performance appeard to be operating bed temperature.